Photoshop CS4 for designers - Barker, Corey; Safari eBooks ([Berkeley, Calif.?] : Kelbytraining : Peachpit Press, 2008)
"This course goes beyond Photoshop as a photography tool and engages your creativity with off-the-wall techniques for creating astounding effects right from scratch."--Resource description page.
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Title from resource description page (viewed March 6, 2009).
Electronic reproduction.
Keywords: Adobe Photoshop; Photography -- Digital techniques; Electronic books